The Fulfillment of Felicity Conditions in Speech Acts in Winfrey’s Speech Learn from Every Mistake - Yuliarti, Indah; Mujiyanto, Januarius; Saleh, Mursid (Universitas Negeri Semarang, 2021)
This study was about fulfilling felicity conditions in speech acts in Winfrey's speech Learn from Every Mistake. This research analyzed each utterance spoken by Winfrey’s speech entitled Learn from Every Mistake. Each utterance is categorized based on five types of speech acts. The felicity of the utterance was analyzed based on Searle's felicity condition theory. This study was a qualitative case study. The research object was Winfrey’s speech entitled Learn from Every Mistake published on YouTube on 18th May 2019. The findings showed that all the utterances in five types of speech act fulfilled the felicity conditions. The consideration came when the utterances were in a joke which meant that the speaker did not sincerely utter the utterances. There was a note when utterances in a joke were felicitous if both the speaker and the hearers truly understood that the utterance was a joke. The last conclusion in felicity condition was in the essential speech act. Based on the analysis, all of the utterances in Winfrey's speech entitled Learn from Every Mistake were felicitous in essential condition. The research finding can be used as a reference in understanding felicity conditions in the speech act.